Nephroprotective activity of the enriched polyphenol extract of Euterpe edulis Martius - Priscylla Maria Martins Cardoso; Renata Alves Mazuco; Lucas Soares Dazzi Macedo; Ariele Abreu Venturini Polese; Maria Eduarda de Souza Barroso; Waléria Gramilich Baratella; Tadeu Uggere de Andrade; Dominik Lenz; Thiago de Melo Costa Pereira; Denise Coutinho Endringer (Universidade de São Paulo, 2020)
Contrast-induced nephropathy (NIC) is directly related to increased morbidity and mortality, and its treatment and prevention might be achieved by the administration of antioxidant products. The juçara palmetto (Euterpe edulis Martius) has fruits rich in phenolic compounds, which are known for their antioxidant activity. This work aimed to evaluate the nephroprotective activity of E. edulis pulp in the NIC animal model. The collected fruits were pulped, their contents of polyphenols and anthocyanins were quantified, and their antioxidant activity were evaluated. The nephroprotective effects were determined based on iodine contrast induction and evaluated by biochemical and histological analyses. The results showed that E. edulis pulp was rich in polyphenols (811 ± 16.7 mg EAG/g) and anthocyanins (181.25 mg/100 g) and had very strong antioxidant activity, as demonstrated by the DPPH (2,2-diphenyl-1-picryl-hydrazyl) method, which revealed an antioxidant activity index (AAI) of 3.4, and the 2,29-azinobis (3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) method, which revealed an IC50 of 0.59 ± 0.03 mg/mL. In the in vivo experiments, E. edulis pulp tended to provide renal protection and reduce renal dysfunction and tubular morphological lesions in mice after the induction of NIC, and these effects were obtained through the antioxidant activities of the polyphenols in the pulp.